(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the impact of using a brain-based learning strategy in the development of aesthetic expression skills among female students of the preparatory stage in Dhi Qar governorate, and the research sample consisted of (76) female students who were divided into an experimental group of (38) female students and a control group of (38) from Abad al-Rahman school, Dhi Qar governorate, the researcher has reached several results, the most important of which are: "There are statistically significant differences between the average scores of pupils of the control group and the experimental group in the development of aesthetic expression skills attributable to the brain-based learning strategy". "There is an effect of teaching using a brain-based learning strategy on the development of aesthetic expression skills in the study sample members for the benefit of the experimental group members"